Elaboration and Quality of Greek Yogurt (labneh) from Buffalo Milk Supplemented with Plus açaí jelly (Euterpe oleracea Mart.) - Silva, Wagner Barreto da; Lourenço-Costa, Vanessa Vieira; Campos, Higo Otávio Brochado; Santos, Wânia Mendonça dos; Bezerra, Andréia Santana; Silva, Jamile Andréa Rodrigues da; Lourenço-Júnior, José de Brito (Journal of Agricultural Studies, 2021)
Buffalo milk has a high nutritional value, with high fat, protein, and mineral levels. Its derivatives yield exceeds by 40% those derived from bovine milk. As a way to take advantage of this quality, Greek yogurt (Labneh) is an alternative to add value to this important product. Thus, this work aims to prepare Greek yogurt with buffalo milk, added with açaí jelly (Euterpe oleracea Mart.), to carry out physical-chemical, microbiological, sensory, and texture profile analyzes in buffalo milk, Greek yogurt, and in açaí jelly. Natural Greek yogurt had an acceptability index of 90.11% and Greek yogurt with açaí jelly, 93.11%, which constitutes an alternative for regional raw material valorization, with excellent acceptability, high nutritional value, and outstanding physical-chemical and microbiological quality. Thus, this derivative is indicated for special programs supported by the City Halls and/or Government of Pará state, as a way of generating income and employment for communities producing buffalo milk and açaí.